Recommended reference books for small and medium-sized libraries and media centers - Graff Hysell, Shannon (Libraries Unlimited, 2008)
"This nationally acclaimed work provides reviews of reference books, CD-ROMs, and Internet sites published in the United States and Canada within a single year, along with English-language titles from other countries"--p. xi.